PENGEMBANGAN BAHAN AJAR TEMATIK INTEGRATIF BERBASIS LINGKUNGAN KELAS V DI MADRASAH IBTIDAIYAH NURUL HAROMAIN KULONPROGO YOGYAKARTA - Yunaini, Norma (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2019)
This research departs from the problem of the still low quality of the thematic learning process in the classroom, and the teacher's ability to develop teaching materials. The main objective of this study was to produce an environment-based thematic learning design in MI Nurul Haromain Kulon Progo Yogyakarta class V in fostering student creativity. This study uses a research and development method or